Holistic Curriculum Development in Islamic Education Institutions in Vocational Schools - Moch. Salman Alfarizi; Khozin (LECTURES: Journal of Islamic and Education Studies, 2024)
The development of a holistic curriculum in Islamic education institutions at vocational schools is a solution to the increasingly complex needs of the world of work. The aim of this research is to determine the development of a holistic curriculum in Islamic education institutions at vocational schools. This research method uses the library research method. The results of this research are that the development of a holistic curriculum at Vocational High Schools (SMK) Islamic Education Institutions provides a number of significant benefits. This curriculum creates a comprehensive and relevant educational approach by integrating academic dimensions, character and practical skills.